Optimization and Performance Test of Oil Spill Dispersant at Bioremediation of Contaminated Soil with Heavy Oil by Bioslurry Technique - Muhammad Abdul Aziz; Mohamad Yani; Agung Dhamar Syakti (JOURNAL OF TROPICAL SOILS, 2020)
Petroleum industry activities produce waste such as petroleum hydrocarbons which damage to the soil environment due to changes in soil physical, chemical and biological properties. Oil Spill Dispersant (OSD) is a product that can break down waste of oil into small parts so that it can be dispersed naturally. Laboratory experiments aimed to find out optimize and performance test of OSD in the process of bioremediation with using bio-slurry technique on contaminated soil with heavy oil was carried out at Laboratory of Surfactant and Bio-energy Research Center (SBRC), Research and Community Service Institute of Bogor Agricultural University on January - August 2018 using contaminated soil with heavy oil. The experiment used Response Surface Method (RSM) with two factors, namely the incubation time factor (X1) and the Dispersant to oil ratio (DOR) (X2). The observed variables were soil Total Petroleum Hydrocarbons (TPH), pH, total microbes, and Chemical Oxygen Demand (COD) at soil solution. The results showed that the treatment of incubation time and its combination with DOR significantly reduced soil TPH, increased soil acidity, and increased soil total B. megaterium, but did not significantly affect on COD in soil solutions. Optimization of OSD with RSM showed that the higher DOR of OSD and the longer the incubation time, the higher also the rate of biodegradation of TPH. The optimum conditions were reached at DOR of 1.16:1 and incubation time of 7 days which were able to degrade soil TPH of 54.30%. The optimum conditions of soil pH (8.825) was reached at DOR of 1:1 and incubation time of 5 days, as well as the optimum conditions of B. megaterium (8.35 log CFU g-1) was reached at DOR of 0.86:1 and incubation time of 7 days. Oil spill dispersant (OSD) increased COD in soil solution in both uncontaminated and contaminated soils with heavy oil.